Kaiju no. 8. 8 - Matsumoto, Naoya, 1982- (Shonen Jump manga., 2023)
"Kafka wants to clean up kaiju, but not literally! Will a sudden metamorphosis stand in the way of his dream? With the highest kaiju-emergence rates in the world, Japan is no stranger to attack by deadly monsters. Enter the Japan Defense Force, a military organization tasked with the neutralization of kaiju. Kafka Hibino, a kaiju-corpse cleanup man, has always dreamed of joining the force. But when he gets another shot at achieving his childhood dream, he undergoes an unexpected transformation. How can he fight kaiju now that he's become one himself?! Reno finally puts his Numbers Weapon training to the test in a live kaiju-combat field test. Meanwhile, Iharu, feeling left behind after witnessing Reno's explosive progress, shifts his focus to improving his own skills--that is, until an abnormality strikes Reno during their neutralization mission and forces Iharu into action!"--Publisher's website.